THE POSITION OF PLATELET MASS INDEX IN DIAGNOSIS IN ACUTE CORONARY SYNDROME PATIENTS ADMITTING TO THE EMERGENCY DEPARTMENT - ÇİÇEK, Ömer Faruk; EKİNGEN , Evren; ZAMAN, Süeda; ŞEYHANLI , Eyyüp Sabri (Göbeklitepe Medical Science Journal, 2024)
Acute coronary syndrome (ACS) describes ischemia and/or infarction situations that occur as a result of sudden decrease in coronary blood flow. In this study, we aimed to investigate the place of the platelet mass index (TKI) value, a new parameter, in the differential diagnosis of cardiac and non-cardiac chest pain in patients presenting to the emergency department with chest pain. In the study, pre-treatment biochemistry, hemogram markers, and electrocardiography (ECG) results of a total of 450 adult patients over the age of 18 who applied to the emergency department of the University of Health Sciences Mehmet Akif İnan Training and Research Hospital with complaints of chest pain between January 2020 and January 2022 were examined. The average age of the patient group was 58,070 (34-78) and there were 224 men and 226 women. It was observed that the platelet mass index value was statistically significant (p<0.001) between the cardiac chest pain group and the non-cardiac chest pain groups. It has been observed that some biochemical markers such as red blood cell width (RDW), MPV (Mean Platelet Volume) and platelet, among the hemogram parameters, have high diagnostic values in diseases such as acute myocardial infarction, renal artery stenosis, diabetes mellitus, hypertension and hyperlipidemia. In our study, it was determined that the MPV values of the patient group diagnosed with ACS (STEMI and NSTEMI) were statistically significant compared to the patient group without cardiac chest pain. It was determined that the platelet count was significant between the STEMI patient group and the non-cardiac chest pain patient group (p<0.001). It was observed that there was no significant difference between the STEMI and NSTEMI patient groups, which are the ACS groups (p = 1).